Underlying determinants of maternal mortality in a rural South African population with high HIV prevalence (2000–2014): A population-based cohort analysis - Tlou, B. (PLOS ONE, 2018)
Introduction Maternal mortality is one of the significant health indicators of any country and it’s a frequent subject in many global heath discussions. Even though the global trends have shown a decrease on maternal mortality, many countries in sub-Saharan Africa failed to achieve the MDG 5 target in 2015.There is no specific single solution for reducing maternal mortality but there is unanimity that a reliable health system with skilled personal is vital for addressing maternal mortality. This study therefore seeks to identify the risk factors for maternal mortality in typical rural sub-Saharan African countries. Method A longitudinal population based cohort study was conducted using data from 2000–2014 in Africa Health Research Institute (AHRI).The Cox regression method was used to assess the influence of selected risk factors using the Mosley-Chen model on maternal mortality. A total of 20701 women aged 15–49 years were included in the study. Results The study found 212 maternal deaths from 32,620 live births with a maternal mortality ratio (MMR) of 650 per 100,000 live births. The main causes of death were Communicable diseases (38.2%), Aids and TB (31%) and Unknown causes (11.8%). An increased risk of death was identified on, poor wealth index (HR 3.92[1.01, 15.3]), period of death 2000–2006(HR32.1 [3.79, 71.5]) and number of deliveries (6.76[2.70, 16.9]) were associated with a high risk of maternal mortality after adjusting for other independent variables included in the study. Conclusion Socio-economic status, number of deliveries and period of death were found to be associated with maternal death in rural South Africa.